Macrozoobenthos of the Olyutorsky Bay (Bering Sea) a quarter of century later: composition, distribution, communities - V. A. Nadtochy; N. V. Kolpakov (Известия ТИНРО)
Results of two bottom grab surveys in the Olyutorsky Bay of the Bering Sea conducted in 1985 (37 stations with 60 samples in the depth range of 20–200 m) and 2012 (26 stations with 48 samples at the depths of 51–270 m) are compared. Average biomass of macrozoobenthos was rather stable: 561.1 ± 95.2 g/m2 in 1985 and 581.3 ± 94.5 g/m2 in 2012. Sea urchins, bivalves and polychaetes dominated by biomass in 1985 (84.7 % of the total biomass for these 3 groups), but sipunculids appeared in the list of the dominant taxonomic groups in 2012 when 91.3 % of the total biomass consisted of the top 4 groups. The main communities of macrozoobenthos practically retained their location and quantitative parameters. There is concluded that composition, distribution and abundance of macrozoobenthos in the Olyutorsky Bay were stable over a quarter of century.